1998
DOI: 10.2190/91w2-njrq-ck3b-n0bw
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related Behaviors among Recently Immigrated and Undocumented Latinas

Abstract: HIV/AIDS research, prevention, and intervention efforts have widened in recent years to include minorities and women, partly in response to the rise of infection among these groups [1]. However, conventional research methods (i.e., random community samples) are likely to exclude more marginalized groups such as undocumented immigrants. We conducted ethnographic interviews of twenty-one recently immigrated and undocumented Latinas regarding their HIV-related risk behaviors, partners risk behaviors, HIV knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…Consistent with other studies, Latinas in rural NC held several misconceptions about the cause and risk factors for cervical cancer [17,18]; however, they did demonstrate an accurate understanding of the importance of Pap screening. Participants alluded to male sexual behaviors, such as extramarital relationships, that were consistent with findings from other studies [8,9,15,16]. The women's perception of their risk for STDs as a result of their partners' behavior, however, was more accurate than previously found.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with other studies, Latinas in rural NC held several misconceptions about the cause and risk factors for cervical cancer [17,18]; however, they did demonstrate an accurate understanding of the importance of Pap screening. Participants alluded to male sexual behaviors, such as extramarital relationships, that were consistent with findings from other studies [8,9,15,16]. The women's perception of their risk for STDs as a result of their partners' behavior, however, was more accurate than previously found.…”
Section: Discussionsupporting
confidence: 83%
“…Because HPV is sexually transmitted, risk factors for cervical cancer in all women involve sexual behavior, with multiple sex partners being the most important determinant for HPV infection [6,7]. Studies have indicated that while most Latinas practice monogamy and refrain from risky sexual behaviors, they are still at particularly high risk for STDs due to low rates of condom use and high rates of multiple partners by their male counterparts [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported that immigrant women from many cultures may be less likely to use condoms because they lack the power in their relationships to insist on condom use (5,54,94). Efforts that focus mainly on condom use to prevent HIV-infection and other sexually transmitted diseases may be less effective if they ignore this.…”
Section: Responsible Sexual Behaviormentioning
confidence: 99%
“…Aneshensel et al report that Mexican-born teens initiated sexual intercourse at a later age than their U.S.-born counterparts and had fewer lifetime sexual partners (4). However, the mean age of first pregnancy was the same for the two groups, owing to lower rates of contraception and pregnancy termination among Latina girls (4).Several authors have reported that immigrant women from many cultures may be less likely to use condoms because they lack the power in their relationships to insist on condom use (5,54,94). Efforts that focus mainly on condom use to prevent HIV-infection and other sexually transmitted diseases may be less effective if they ignore this.…”
mentioning
confidence: 99%
“…Research examining people who are HIV-suggests that perceptions of safer sex negotiation are influenced primarily by the nature of the relationship with the partner [6][7][8][9][10][11][12][13]24], and by attitudes regarding condoms and condom use [4-6, 11-13, 15, 24]. In addition, the little research that has examined HIV-women at heterosexual risk suggests that their perceptions are also influenced by concerns regarding conflict with or threat from a partner [4,5,7,15].…”
mentioning
confidence: 99%